GEANT4 based simulation study of converter and direct target design and optimization of target for 99Mo production using 30 MeV electron linear accelerator. (July 2022) - Shaikh, Aqsa; Dixit, Tanuja; Deshpande, Abhay; Krishnan, R.
Abstract: A 30 MeV, 5–10 kW beam power electron linac is under development at SAMEER for radio-isotope production. An enriched 100 Mo target will be irradiated to produce 99 Mo which will be eluted to give 99m Tc. Two approaches of 100 Mo target irradiation -converter and direct are studied using GEANT4 simulations. The main aim of this study is to optimize the 100 Mo target geometry for maximum yield. It is observed that direct target irradiation gives better activity as compared to converter target approach. Highlights: Production of 99 Mo isotope using electron linear accelerator technology. GEANT4 based study of direct and converter target irradiation approach. Optimization of target geometry to maximize the 99 Mo activity. Higher specific activity obtained by direct target irradiation method.